Fundamental Insights into the Reductive Covalent Cross-Linking of Single-Walled Carbon Nanotubes - Schirowski, Milan; Abellan Saez, Gonzalo; Nuin Pla, Neus Edurne; Pampel, Jonas; Dolle, Christian; Wedler, Vincent; Fellinger, Tim-Patrick; Spiecker, Erdmann; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2018)
Single-walled carbon nanotubes (SWCNT) have been covalently cross-linked via a reductive functionalization pathway, utilizing negatively charged carbon nanotubides (KC4). We have compared the use of difunctional linkers acting as molecular pillars between the nanotubes, namely p-diiodobenzene, p-diiodobiphenyl as well as benzene-4,4’-bis(diazonium) and 1,1’-biphenyl-4,4’-bis(diazonium) salts as electrophiles. We have employed statistical Raman spectroscopy (SRS), a forefront characterization tool consisting of thermogravimetric analysis coupled with gas chromatography and mass spectrometry (TG-GC-MS), and aberration-corrected high resolution transmission electron microscopy image series at 80kV to unambiguously demonstrate the covalent binding of the molecular linkers. The present study shows that the SWCNT functionalization using iodide derivatives leads to the best results in terms of bulk functionalization homogeneity (Hbulk) and degree of addition. Phenylene linkers yield the highest degree of functionalization, whereas biphenylene units induce a higher surface area with an increase in the thermal stability and an improved electrochemical performance in the oxygen reduction reaction (ORR). This work illustrates the importance of molecular engineering in the design of novel functional materials and provides important insights into the understanding of basic principles of reductive cross-linking of carbon nanotube
Keywords: cross-linking; SWCNT; covalent functionalization; diazonium salt; TG-MS

Shell-by-Shell functionalized nanoparticles as radiosensitizers and radioprotectors in radiation therapy of cancer cells and tumor spheroids - Wedler, Vincent; Stiegler, Lisa; Gandziarowski, Teresa; Walter, Johannes; Peukert, Wolfgang; Distel, Luitpold; Hirsch, Andreas; Klein, Stefanie (Colloids and Surfaces B: Biointerfaces, 2025)
Shell-by-Shell (SbS)-functionalized NPs can be tailor-made by combining a metal oxide NP core of choice with any desired phosphonic acids and amphiphiles as 1st or 2nd ligand shell building blocks. The complementary composition of such highly hierarchical structures makes them interesting candidates for various biomedical applications, as certain active ingredients can be incorporated into the structure. Here, we used TiO2 and CoFe2O4 NPs as drug delivery tools and coated them with a hexadecylphosphonic acid and with hexadecyl ammonium phenolates (caffeate, p-coumarate, ferulate), that possess anticancer as well as antioxidant properties. These architectures were then incubated in 2D and 3D cell cultures of non-tumorigenic and tumorigenic breast cells and irradiated to study their anticancer effect. It was found that both, the functionalized TiO2 and CoFe2O4 NPs acted as strong protective agents in non-tumorigenic spheroids. In contrast, the functionalized CoFe2O4 NPs induce a higher damage in irradiated tumor spheroids compared to the functionalized TiO2 NPs. CoFe3O4 NPs act additionally as radiosensitizing agents to the tumor spheroids. The radio-enhancement of the CoFe2O4 NPs is due to the generation of highly toxic hydroxyl radicals during X-ray irradiation. The irradiation exposed the CoFe2O4 surface, releasing the anticancer drugs into the cytoplasm and making the surface Co2+ ions accessible. These surface ions catalyze the FENTON reaction. This combination of radiosensitizer and anticancer drug delivery proved to be a very effective nanotherapeutic in 2D and 3D cell cultures of breast cancer cells.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Amphiphiles; CoFe; Phenolic acids; Radioprotectors; Radiosensitizers; Shell-by-Shell functionalization; TiO

Tunable Composition of Mixed Self-Assembled Shell-by-Shell Structures on Nanoparticle Surfaces - Eigen, Andreas; Stiegler, Lisa; Gradl, Susanne; Schneider, Vanessa; Wedler, Vincent; Gaß, Henrik; Müller, Lukas; Sarcletti, Marco; Heinrich, Markus; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces, 2022)
The formation of mixed shell-by-shell (SbS) systems with tunable shell compositions is demonstrated by using molecular self-assembly driven by chemical recognition motifs. Aluminum oxide nanoparticles (AlOx-NPs) act as template surface for a self-assembled monolayer (SAM) of either partially fluorinated fluoroalkyl or alkyl chained phosphonic acid derivatives or defined stoichiometric mixtures of those. By providing an equimolar mixture of corresponding fluoroalkyl and alkyl-chained amphiphiles in water, the stoichiometry of underlaying mixed SAM on the NP-surface preferentially directs the composition of the secondary self-assembly. The composition of the shell-by-shell assemblies is studied by high performance liquid chromatography and fluorescence spectroscopy. The concept allows the formation of NP-templated vesicle-like bilayer structures, even consisting of orthogonal chain structures in tunable composition driven by chemical recognition and hydrophobic segregation.
Created from Fastlane, Scopus look-up
Keywords: hydro-; fluoro-; lipophilic/phobic; nanoparticles; self-assembly; shell-by-shell architectures; surface chemistry